Generalized Fragility Relationships with Local Site Conditions for Probabilistic Performance-based Seismic Risk Assessment of Bridge Inventories - Lau, D.T.; Vishnukanthan, K.; Waller, C.L.; Sivathayalan, S. (Civil Engineering Dimension, 2012)
The current practice of detailed seismic risk assessment cannot be easily applied to all the bridges in a large transportation networks due to limited resources. This paper presents a new approach for seismic risk assessment of large bridge inventories in a city or national bridge network based on the framework of probabilistic performance based seismic risk assessment. To account for the influences of local site effects, a procedure to generate site-specific hazard curves that includes seismic hazard microzonation information has been developed for seismic risk assessment of bridge inventories. Simulated ground motions compatible with the site specific seismic hazard are used as input excitations in nonlinear time history analysis of representative bridges for calibration. A normalizing procedure to obtain generalized fragility relationships in terms of structural characteristic parameters of bridge span and size and longitudinal and transverse reinforcement ratios is presented. The seismic risk of bridges in a large inventory can then be easily evaluated using the normalized fragility relationships without the requirement of carrying out detailed nonlinear time history analysis.